Stride-to-stride lower limb sagittal-plane joint angle variability of walking across inclinations - Chiang, Chuan-Chih (2024)
As walking serves as an indicator of multiple health conditions and quality of life, it is important to obtain a thorough understanding of walking, specifically, gait. When walking in the community, it is inevitable to walk on uneven surfaces, including slopes. The sloped walking is more imbalanced compared to level walking and several alterations in biomechanics are required to adapt to its perturbations. Since the trunk and pelvis manage their position according to the earth’s vertical during sloped walking, the lower limbs have to interact with this postural adjustment, leading to changes in kinematics. During walking, the sensorimotor system constantly tunes the movement patterns, and the variance exists from stride to stride. The variability within movement has been found to have a deterministic origin, and it alters when encounters perturbations or new tasks. An increased variability has been correlated to decreased balance performance or enhanced adaptability of movement strategy. Extremely high or low variability is considered an impairment or unhealthy condition. So far, there haven’t been many studies about gait variability during sloped walking and more studies are mandatory to reveal how sensorimotor strategy alters. As a result, this study aims to investigate the stride-to-stride lower limb sagittal-plane joint angle variability during uphill and downhill walking. The participants were healthy adults (Age: 34.2±7.6, 13 females). They were asked to walk on the treadmill at a constant self-selected speed and at 0°, ±2°, ±4°, ±6°, and ±12° inclinations. Motion data was collected by an 8-camera motion capture system with a sampling rate of 200 Hz. Plug-in-Gait lower body model was applied for kinematic analysis. Thirty participants’ data were included in the analysis. An automatic gait event detection based on marker displacement was adopted to estimate the gait events. The sagittal-plane joint angle variability was calculated through a linear method, mean standard deviation, and a non-linear method, sample entropy. The results showed that the inclinations had significant effects on the spatiotemporal parameters and the lower limb sagittal-plane joint angle variability. The alterations in the spatiotemporal parameters indicated that the participants favored a more conservative gait during downhill and steep uphill walking. Stride-to-stride sagittal-plane joint angle variability generally increased as the inclinations increased. Specifically, the amount and the structure of the sagittal-plane joint angle variability increased during downhill walking compared to level walking. On the other hand, during uphill walking, the amount of the sagittal-plane joint angle variability incrementally increased as the inclination increased, while the structure of the sagittal-plane joint angle variability decreased at lower inclines and increased at the highest inclines. Overall, the results indicated that the healthy adults used a more flexible movement strategy during sloped walking. The alteration in the sagittal-plane joint angle variability suggested that the sensorimotor strategy was task-specific, and it might change in response to the balance perturbations, muscular coordination, and power demands during walking on inclined surfaces.